Partial Remodeling after Conservative Treatment of Trampoline Fractures in Children - Laura Zaccaria; Enno Stranzinger; Theodoros Xydias; Sabine Schaedelin; Kai Ziebarth; Mike Trück; Vivienne Sommer-Joergensen; Christoph Aufdenblatten; Peter Michael Klimek (MDPI AG, 2023)
(1) Background: Trampoline fractures (proximal tibia fracture with positive anterior tilt) are increasing. This study represents the first attempt to determine the extent of remodeling in these fractures after conservative treatment (2) Methods: This Swiss prospective multicenter study included children aged 2 to 5 years with a trampoline fracture who were radiologically examined on the day of the accident and after one year. In addition, the anterior tilt angle was compared between the injured and unaffected tibia. Remodeling was defined as complete (final anterior tilt angle ≤ 0°), incomplete (smaller but still >0°), or no remodeling. (3) Results: The mean extent of remodeling was −3.5° (95% CI: −4.29°, −2.66°, p < 0.001). Among the 89 children included in the study, 26 (29.2%) showed complete, 63 (70.8%) incomplete, and 17 patients (19.1%) no remodeling. Comparison of the anterior tilt angles between the fractured and healthy tibia showed that the anterior tilt angle on the fractured leg was, on average larger by 2.82° (95% CI: 2.01°, 3.63°; p < 0.001). (4) Conclusions: Although the anterior tilt angle decreased during the study period, the majority of patients showed incomplete remodeling. In contrast, children with radiological examinations >1 year after the trauma showed advanced remodeling, suggesting that one year is too short to observe complete remodeling.